2014
DOI: 10.4274/jcrpe.1404
|View full text |Cite
|
Sign up to set email alerts
|

One Base Deletion (c.2422delT) in the TPO Gene Causes Severe Congenital Hypothyroidism

Abstract: Ob­jec­ti­ve: Congenital hypothyroidism (CH) is the most common neonatal endocrine disorder and mutations in the TPO gene have been reported to cause CH. Our aim in this study was to determine the genetic basis of CH in two affected individuals coming from a consanguineous family.Methods: Since CH is usually inherited in autosomal recessive manner in consanguineous/multi-case families, we adopted a two-stage strategy of genetic linkage studies and targeted sequencing of the candidate genes. First, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In the largest series of patients with TPO gene mutations (17), a study conducted in Israel, no significant correlation was observed between the specific type of mutation and the severity of clinical presentation. Further case reports for specific mutations should be accumulated in order to gain more detailed insights into the broad phenotypic variations in this entity (21,22). …”
Section: Discussionmentioning
confidence: 99%
“…In the largest series of patients with TPO gene mutations (17), a study conducted in Israel, no significant correlation was observed between the specific type of mutation and the severity of clinical presentation. Further case reports for specific mutations should be accumulated in order to gain more detailed insights into the broad phenotypic variations in this entity (21,22). …”
Section: Discussionmentioning
confidence: 99%
“…The first reported mutation in TPO gene was a homozygous GGCC insertion-duplication at position c.1186 in the exon 8 [54]. A homozygous TPO deletion (c.2422delT), associated with total iodine organification defect and abolition of TPO enzyme function [55], was detected in CH affected siblings from a consanguineous family [56]. A c.2268dup nonsense mutation in the exon 13 of the TPO gene had been reported to be common amongst dyshormonogenetic congenital hypothyroidism patients from Taiwan [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Three cases born to a consanguineous Turkish family were ascertained through our studies on the genetics of CH. [16][17][18][19][20][21][22][23][24][25][26] The older sister was first diagnosed at the age of 8 months with hormone values of thyroid-stimulating hormone (TSH) 132 mIU/L (normal 0.35-5.5), free thyroxine (fT 4 ) 0.3 ng/dL (normal 0.8-2.0), and T 3 20 ng/dL (normal 80-120). Thyroid ultrasonography showed a thyroid gland of normal size and location.…”
Section: Subjectsmentioning
confidence: 99%
“…To investigate genetic background of CH, we developed a two-tier strategy combining genetic linkage studies and full sequencing of candidate genes in familial cases and identified several mutations to date in different CH genes. [16][17][18][19][20][21][22][23][24][25][26] In the current study we aimed to determine genetic cause of CH in a consanguineous family with three affected siblings. Here we report a homozygous duplication (c.1184_1187dup4) in the TPO gene detected in all cases and associated clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%